pengaruh kualitas layanan mobile banking terhadap kepuasan nasabah pada pt. bank aceh syariah cabang bireuen - NURUL ULFA (Jurnal Syariah dan Ekonomi Islam, 2023)
The rapid development of technology is directly utilized by the banking industry, especially Islamic banking by bringing up digital product innovations. Mobile banking is one of a series of technological advances that aim to facilitate customer transactions and provide information to customers through the features provided. In the development of digital products, service quality is the most important thing because it is directly felt by customers, so that it will form customer satisfaction in using a product. The method used in this study is quantitative research method. The variables of his research are service quality (X) and satisfaction (Y). The data collection technique was carried out through a questionnaire, the sample taken amounted to 82 respondents using incidental sampling techniques. The analysis tool uses IBM SPSS Statistic 22 which includes validity tests, reliability tests, classical assumption tests, simple linear regression analysis, determination coefficients, T hypothesis tests. The results showed that the quality of mobile banking services affects customer satisfaction at PT. Bank Aceh Syariah Bireuen Branch, this is seen from the results of the t count value of mobile banking service quality on customer satisfaction of 2,054 with a significance of 0,043 < 0,05 while the t table value is 1,663 < 2,054 t count. So the value of t count is greater than t table, this shows that Ho is rejected and Ha is accepted which states that the quality of mobile banking services has a significant effect on customer satisfaction.